Powers all new powers - Bendis, Brian Michael 1967-; Oeming, Michael Avon (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC., 2016)
"The Eisner Award-winning POWERS tells the story of homicide detectives Christian Walker and Deena Pilgrim, who are assigned cases specifically involving powers. If a superhero falls dead from the sky or a super villain is found dead in the gutter, it's up to Walker and Pilgrim to solve the case. But having barely survived the most harrowing case of their careers and discovering government corruption of the highest level, Walker and Pilgrim are now faced with the most difficult decision they've ever had to make. Plus: the discovery of a power no one has ever seen before!"--amazon.com